Antimicrobial Screening of Some Derivatives of Methyl ?-D-Glucopyranoside: Antimicrobial Studies of Methyl Gloucopyranoside Derivatives - Kabir, Abul K. M. S.; Kawsar, Sarkar M. A.; Bhuiyan, Mohammad M. R.; Rahman, Md. Safiqur; Chowdhury, Mohammad E. (Biological Sciences - PJSIR, 2009)
In vitro antimicrobial functionality test of methyl 4,6-O-cyclohexylidene-a-D-glucopyranoside and its twelve acylated derivatives against ten human pathogenic bacteria and six phytopathogenic fungi comparative to Ampicillin and Nystatin revealed the tested chemicals to possess moderate to good antibacterial and antifungal activity and to be more effective against fungal phytopathogens. Many of these chemicals exhibited better antimicrobial activity than the standard antibiotics. Minimum Inhibition Concentration (MIC) of methyl 4,6-O-cyclohexylidene-2-O-myristoyl- 3-O-palmitoyl-a-D-glucopyranoside against Bacillus cereus, Bacillus subtilis and Staphylococcus aureus was 25, 12.5 and 25 ?g/disc, respectively.